2008
DOI: 10.1097/rli.0b013e3181817b3d
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography, Positron Emission Tomography, Positron Emission Tomography/Computed Tomography, and Magnetic Resonance Imaging for Staging of Limited Pleural Mesothelioma

Abstract: PET/CT makes it possible to stage patients with limited MPM with high accuracy and low interobserver variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 37 publications
0
50
0
5
Order By: Relevance
“…In patients with late diagnosis and early stage MPM, the occult metastasis rate defined by PET-CT is 15%. Moreover, in PET-CT, high standardized uptake value ratios (SUVmax) are related to poor prognosis (Flores et al, 2003;Plathow et al, 2008). In our study, no relevance was detected between the SUVmax value shown by PET-CT before chemotherapy and progressionfree survival.…”
Section: Discussionmentioning
confidence: 36%
“…In patients with late diagnosis and early stage MPM, the occult metastasis rate defined by PET-CT is 15%. Moreover, in PET-CT, high standardized uptake value ratios (SUVmax) are related to poor prognosis (Flores et al, 2003;Plathow et al, 2008). In our study, no relevance was detected between the SUVmax value shown by PET-CT before chemotherapy and progressionfree survival.…”
Section: Discussionmentioning
confidence: 36%
“…It can play a role in differentiating benign from malignant lesions and help target the most suitable lesion for biopsy (10). In addition, it has been shown to be effective in pre-operative imaging, particularly with regards to detecting distant metastases (11,12). Given the diffuse, infiltrative nature and asymmetric growth pattern of MPM, measuring response to treatment with CT is extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In order to stage MPM and decide on treatment options, imaging modalities such as MSCT, MRI, and positron emission tomography-computed tomography (PET-CT) are employed (8,9). Due to the diffusion of water molecules in tissues, DWI can reveal tissue characteristics.…”
Section: Discussionmentioning
confidence: 99%